Resolving Land Sale Disputes through Legal Advocacy: A Normative Study of Judicial Reasoning in Plural Legal Systems - M. Yazid Fathoni; Diangsa Wagian; Lalu Hadi Adha (Indonesian Journal of Advocacy and Legal Services, 2025)
The transfer of land rights is a classic problem, but the legal basis that validates its validity remains ambiguous to date.  Although Government Regulation Number 24 of 1997 concerning Land Registration emphasizes that the transfer of land rights is executed using a PPAT deed, judges sometimes have varying legal considerations when deciding the issue of the validity of the transfer of land rights. The validation of these considerations is sometimes also based on the Burgerlijk Wetboek, or sometimes based on Customary/Adat Law. Based on the Morality-Positivism theory, this article will explore how judges should decide a case that falls into the category of "hard cases" regarding the issue of the transfer of land rights in Indonesia, including the legal sources that are used as references. The research method in this article is the normative legal research method. Based on the Dworkin’s theory (law as integrity) and seeing positive law still with moral judgment in it (moral-positivism), judges in deciding cases can use discretion in deciding hard cases. However, in a theoretical context, judges do not have absolute discretion or absolute freedom (independence) in deciding cases. The freedom of judges is within the limits of a circle, which Ronald Dworkin called the metaphor of the hole in the doughnut. Therefore, the judge's decision must not be separated from the spirit and principles of the Basic Agrarian Law. With the Morality of Law, judges cannot decide cases with policy (inclusive positivist), but can only base their decisions on the principles to maintain coherence